2009
DOI: 10.1007/s11743-009-1170-2
|View full text |Cite
|
Sign up to set email alerts
|

Styrene and Phenylethanol Adsolubilization of a Polymerizable Gemini Surfactant

Abstract: A polymerizable gemini surfactant was used to adsolubilize styrene and phenylethanol, representing less and more polar organic solutes, respectively, in order to evaluate the impact of admicellar polymerization on the adsolubilization process. Adsolubilization was also evaluated using a polymerizable monomeric surfactant and conventional surfactant for comparison purposes. The main results were that: (1) polymerized and unpolymerized admicelles showed similar adsolubilization potentialvalidating the use of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…Results showed an inverse relationship between K adm and X aq values for every surfactant and surfactant-linker mixtures. With increasing of X aq , reductions of K adm values were observed which is in an agreement with previous studies [6,21]. Previous reports suggest that styrene partitions in the palisade layer of the surfactant admicelle.…”
Section: Styrene Adsolubilization Resultssupporting
confidence: 92%
“…Results showed an inverse relationship between K adm and X aq values for every surfactant and surfactant-linker mixtures. With increasing of X aq , reductions of K adm values were observed which is in an agreement with previous studies [6,21]. Previous reports suggest that styrene partitions in the palisade layer of the surfactant admicelle.…”
Section: Styrene Adsolubilization Resultssupporting
confidence: 92%
“…Scope for further work at laboratory level include reducing the time required for attaining equilibrium for the admicelle formation and adsolubilization process. The use of polymerizable gemini surfactants has been reported,, but not for application on textile substrates. The future of ADPM in textile industry can include production of stain‐resistant or water‐repellent napkins, which will find applications in catering and hospitality services.…”
Section: Resultsmentioning
confidence: 99%
“…The palisade region is the region between the surfactant head groups and the core region, thus this region exhibits an intermediate polar region. Studies have indicated that the locus of solubilization in admicelles impacts the nature of adsolubilization and that organic solutes tend to partition into the region that has polarity similar to the solute [12,14,17,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%